STUDENT AND SCHOOL CORRELATES OF MATHEMATICS ACHIEVEMENT: MODELS OF SCHOOL PERFORMANCE BASED ON PAN‐ CANADIAN STUDENT ASSESSMENT - Anderson, John; Rogers, W. Todd; Klinger, Don; Ungerleider, Charles; Glickman, Victor; Anderson, Barry (Canadian Journal of Education/Revue canadienne de l’éducation, 2006)
This study explored the relationships between student achievement and student, school and home variables from the pan‐Canadian assessment program administered by the Council of Ministers of Education Canada (CMEC): the School Achievement Indicators Program (SAIP) Mathematics 2001. The study also evaluated the datasets used in relationship to their utility for statistical modeling of school performance. Student beliefs about mathematics are positively related to mathematics achievement for both age groups and for both domains of mathematics. As students’ use of instructional supports (parental assistance with mathematics homework, computers in the mathematics classroom) increases, there is an associated decrease in mathematics scores. Key words: student achievement, school performance, multilevel modeling. Dans cet article, les auteurs explorent les relations entre le rendement scolaire et certaines caractéristiques des élèves, des écoles et de l’environnement familial à partir des données du programme d’évaluation pancanadien du Conseil des ministres de lʹÉducation (Canada) (CMEC), le Programme d’indicateurs du rendement scolaire (PIRS) 2001 en mathématiques. L’étude évalue également les bases de données au regard de leur pertinence pour la modélisation statistique de la performance scolaire. Les auteurs notent une corrélation directe entre les idées que se font les élèves au sujet des mathématiques et le rendement en mathématiques tant pour les groupes d’âge que pour les domaines des mathématiques. Plus les élèves font appel à du soutien pédagogique (aide des parents pour les devoirs de mathématiques, ordinateurs dans les classes de mathématiques), plus les notes en mathématiques diminuent. Mots clés : rendement des élèves, performance scolaire, modélisation à multiples niveaux.